Les stéréotypes dans la zoo-anthroponymie française et chinoise - Lian Chen (Itinéraires)
In any language, the lexicon is the reflection of a society and a culture that gives a specific status to men, women and animals. The study of lexical stereotypes “animalising” humans, reveals a kind of anthropocentrism in Chinese and French zoo-anthroponymies, in despite of some differences linked to the philosophical and religious substratum. Thus and so some speciesism is manifested in the idiomatic expressions of the two languages. Our study is based on a corpus of French and Chinese idiomatic expressions relating to zoo-anthroponymies, established from specialized Chinese and French dictionaries.